Interleukin‐9 over‐expression and T helper 9 polarization in systemic sclerosis patients. (23rd August 2017) - Guggino, G.; Lo Pizzo, M.; Di Liberto, D.; Rizzo, A.; Cipriani, P.; Ruscitti, P.; Candore, G.; Gambino, C.M.; Sireci, G.; Dieli, F.; Giacomelli, R.; Triolo, G.; et al.
Summary: T helper 9 (Th9) cells and interleukin (IL)‐9 are involved in the pathogenesis of several autoimmune diseases. The exact role of IL‐9 and Th9 cells in patients with systemic sclerosis (SSc) have not yet been studied adequately. IL‐9, IL‐9R, transcription factor PU.1 (PU.1), IL‐4, thymic stromal lymphopoietin (TSLP) and transforming growth factor (TGF)‐β expression were assessed in skin and kidney biopsies of SSc patients and healthy controls (HC) by immunohistochemistry (IHC). The cellular source of IL‐9 was also analysed by confocal microscopy analysis. Peripheral IL‐9‐producing cells were also studied by flow cytometry. The functional relevance of IL‐9 increased expression in SSc was also investigated. Our results demonstrated a strong expression of IL‐9, IL‐9R, IL‐4, TSLP and TGF‐β in skin tissues of patients with both limited and diffuse SSc. IL‐9 expression was observed mainly in the context of skin infiltrating mononuclear cells and keratinizing squamous epithelium. IL‐9 over‐expression was also observed in renal biopsies of patients with SSc. IL‐9 producing cells in the skin were identified as Th9 cells. Similarly, Th9 cells were expanded and were the major source of IL‐9 among SSc peripheral blood mononuclear cells (PBMC), their percentage being correlated directly with the modified Rodnan skin score. Infiltrating mononuclear cells, mast cells and neutrophils expressed IL‐9R. In in‐vitro studies stimulation with rIL‐9 significantly induced NET (neutrophil extracellular traps) release by dying cells (NETosis) in neutrophils, expansion of mast cells and increase of anti‐systemic scleroderma 70 (Scl70) production by B cells. Our findings suggest that Th9 cells and IL‐9 could be implicated in the pathogenesis of SSc. Abstract : IL‐9 and Th9 cells are expanded in the skin, kidney and peripheral blood of SSc patients. IL‐9 pathway may play an important role in SSc and should be considered as potential therapeutic target in SSc.